2015
DOI: 10.1371/journal.pone.0141802
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and Distribution of Marrow Stem Cells in Flex-Flow Environments Demonstrate Support of the Valvular Phenotype

Abstract: For treatment of critical heart valve diseases, prosthetic valves perform fairly well in most adults; however, for pediatric patients, there is the added requirement that the replacement valve grows with the child, thus extremely limiting current treatment options. Tissue engineered heart valves (TEHV), such as those derived from autologous bone marrow stem cells (BMSCs), have the potential to recapitulate native valve architecture and accommodate somatic growth. However, a fundamental pre-cursor in promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Valve cells are particularly challenging in this regard, since harvesting cells from a patient is considered to be extremely invasive if not impossible. Therefore, a suitable VEC facsimile would need to be derived from a different source, such as bone marrow stem cells (Rath et al 2015), peripheral blood endothelial progenitor cells (EPCs), umbilical cord blood EPCs, or possibly induced pluripotent stem cells (IPSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Valve cells are particularly challenging in this regard, since harvesting cells from a patient is considered to be extremely invasive if not impossible. Therefore, a suitable VEC facsimile would need to be derived from a different source, such as bone marrow stem cells (Rath et al 2015), peripheral blood endothelial progenitor cells (EPCs), umbilical cord blood EPCs, or possibly induced pluripotent stem cells (IPSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical heart valves require patients to be on life-long anticoagulant medication; bioprosthetic valves are less durable and more prone to re-calcification. Scientists and engineers have been exploring alternative treatments such as tissue engineered heart valves using bioreactor systems to deliver the proper flow, flex, and stretch conditioning (116,117).…”
Section: Our Laboratory's Experience In Valve Regenerative Medicinementioning
confidence: 99%
“…Some of the major in-house findings of tissue engineered heart valves show that when bone marrow stems cells seeded in scaffolds are exposed to a combination of flex and flow environments, the shear stresses from both flex and flow conditions generated a significantly higher amount of collagen compared flex only or flow only samples. In addition, under static (no flow) conditions, very little collagen is produced (116). This suggests that physiologically relevant flex-flow conditions promote early valvular tissue matrix development.…”
Section: Our Laboratory's Experience In Valve Regenerative Medicinementioning
confidence: 99%
“…Since then, PGA, PGA/PLA hybrids, and their copolymer PLGA have been used in a variety of studies regarding the fabrication of functional, bioresorbable leaflet scaffolds . More recent studies have utilized these scaffolds to observe cellular behavior and mechanical properties . One group studied bone marrow stem cells seeded on PGA:PLLA scaffolds under different stress conditions, such as steady flow, cyclic flexure, and a combination of the two conditions, and found that the cells exhibited endothelial and myofibroblast phenotypes similar to valves under a combination of steady flow and cyclic flexure .…”
Section: Application Of Biomaterials To Heart Valve Tissue Engineeringmentioning
confidence: 99%
“…More recent studies have utilized these scaffolds to observe cellular behavior and mechanical properties . One group studied bone marrow stem cells seeded on PGA:PLLA scaffolds under different stress conditions, such as steady flow, cyclic flexure, and a combination of the two conditions, and found that the cells exhibited endothelial and myofibroblast phenotypes similar to valves under a combination of steady flow and cyclic flexure . Another group found that prolonged tissue culture reduced retraction of the tissue engineered leaflets that typically lose mechanical integrity due to rapid degradation of the PGA scaffold, and suggested that this resulted from an increased amount of GAGs in the tissue …”
Section: Application Of Biomaterials To Heart Valve Tissue Engineeringmentioning
confidence: 99%